Acute HIV Seroconversion Presenting with Active Tuberculosis and Associated with High Levels of T-Regulatory Cells - Sued, Omar Gustavo (2011)
A patient with well-defined acute HIV infection who developed concomitant pulmonary tuberculosis during the retroviral acute syndrome is reported here. In this patient high levels of T-regulatory cells (Tregs) and a low proliferation response to M. tuberculosis were initially detected, which normalized throughout follow-up. This case calls for the consideration of tuberculosis in patients in the early stages of HIV, and emphasizes the need for further study of the potential causal relationship between Treg cells and the risk of TB reactivation in HIV patients.